THE IMPACT OF COVID-19 PANDEMIC ON THE TOURISM SECTOR IN INDONESIA - Jan Horas Veryady Purba; Ritha Fathiah; Steven Steven (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2021)
The tourism is one of the strategic sectors and has an important role as a source of foreign exchange and encourages national economic growth. Since March 2020, the Covid-19 pandemic has begun to enter Indonesia, and the cumulative infection curve has not sloped, and is still increasing exponentially until now. This phenomenon has resulted in a contraction in the Indonesian economy or created negative economic growth, as well as creating very bad conditions for the tourism sector in Indonesia. This study aims to examine the influence of the Covid-19 pandemic on tourism and its implications for economic growth in Indonesia. The data used are quarterly time series data before and after the Covid-19 Pandemic (2018-2020). This study uses a regression equation model that is estimated by using ordinary least square (OLS). Secondary data used are data air transport and hotel accommodation, as a proxy for tourism variables. The results show that the Covid-19 Pandemic has a negative effect on Indonesian tourism, and has negative implications for Indonesia's GDP. From the simulation results, the findings of this study also calculate the amount of potential lost in the Turism and Indonesian economy during the Covid-19 Pandemic.